The volatile oil of Acorus tatarinowii schott significantly attenuates neuroinflammatory damage in a rat model of tourette syndrome by inhibiting the p38 MAPK/NLRP3/STAT3 signaling pathway - Wei, Xing; Sun, Kexin; Feng, Peng; Huang, Shuang; Jiang, Bing; Cui, Min; Chen, Yuanhuan; Xue, Fuchun; He, Yuezhen; Yao, Jingxi; Shang, Jing; Mei, Hao; et al. (Frontiers in Pharmacology, 2025)
BackgroundAcorus tatarinowii Schott holds a prominent position in Traditional Chinese Medicine, with its earliest record found in the ancient Chinese pharmacopeia, the Shennong’s Classic of Materia Medica. It has been widely used for various central nervous system diseases. VOA has been shown to reduce neuroinflammation and repair neurons. However, the in vivo mechanisms by which this volatile oil alleviates neuroinflammation caused by Tourette syndrome remain unclear.PurposeThis study aims to investigate the effects and molecular mechanisms of VOA intervention in TS, providing scientific evidence for the potential therapeutic role of VOA in TS and paving the way for new treatment strategies.MethodsForty-eight 3-week-old standard deviation rats were divided into a Blank group (n = 8) and a Model group (n = 40). After establishing the Tourette Syndrome animal model, the Model group rats were randomly divided into the Model, Tiapride, VOA, SB203580 and VOA + SB203580 groups. Following model induction, the respective treatments were administered continuously for 4 weeks. At the end of the intervention, Nissl staining was used to observe neuronal structure, and Enzyme-Linked Immunosorbent Assay, immunofluorescence, immunohistochemistry, RT-qPCR and WB were performed to determine the levels of inflammatory factors and protein expression.ResultsNissl staining showed that VOA significantly improved neuronal structure compared to the Model group. Compared to the Model group, the Tiapride, VOA, SB203580 and VOA + SB203580 groups had significantly reduced levels of TNF-α, IL-6, CD11b, COX-2, caspase-1, p38 MAPK, p-p38 MAPK, STAT3, p-STAT3, NLRP3, and GSDMD (P < 0.01 or P < 0.05) and significantly increased levels of IL-10 and CD163 (P < 0.01 or P < 0.05).ConclusionVOA significantly alleviates neuroinflammation in TS rats by modulating the activity of the p38 MAPK/NLRP3/STAT3 signaling pathway, thereby improving the pathological characteristics of TS. These findings suggest that VOA could be a potential candidate for treating TS and other neuroinflammation-related diseases.